Дозиметры энергетической освещенности ультрафиолетового излучения типа "Тензор" - Butenko, V. K.; Dobrovolskiy, Yu. G.; Shabashkevich, B. G.; Yurev, V. G.; Shabashkevich, B. G. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
A group of dosimeters for ultraviolet and visible radiation — “Tenzor‑51”, “Tenzor‑52”, and “Tenzor‑53” — has been developed in accordance with the requirements of current regulatory documentation. The basic relative measurement error of these dosimeters does not exceed ±10%.